-n/12=12/6

Simple and best practice solution for -n/12=12/6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -n/12=12/6 equation:



-n/12=12/6
We move all terms to the left:
-n/12-(12/6)=0
We add all the numbers together, and all the variables
-n/12-2=0
We multiply all the terms by the denominator
-n-2*12=0
We add all the numbers together, and all the variables
-1n-24=0
We move all terms containing n to the left, all other terms to the right
-n=24
n=24/-1
n=-24

See similar equations:

| f(-10)=-10^2+2(-10)-10 | | 12-10=14t+2 | | s-93/2=3 | | F(x)=13-7x | | m/9=11/3 | | (2x+4/5)=6 | | 8t+80=12t | | 3(-5y-4)-2y=-29 | | Y=-101x | | 60q+11=-13 | | 16x^2+12.8x+3.2=0 | | 3y+13+4y+5=123 | | 2.5=45n=18 | | x^2=505 | | x+5.8=7.39 | | 12t=-8t+80 | | 24=2a+10​ | | -6q+21=-63 | | 5(3c2)-7c=40-2c | | 4+8q=60 | | x/3-5=4)4 | | y−7=15 | | 12t=80-8t | | 4r-41=31 | | l×+6l=8 | | 18+23h= | | −5x2+10x=5 | | 3-2x(x+3)=x-18 | | 4+7p=46 | | t–5.3=14.1 | | -7x=-35+140 | | 6.4x-7.5=37.3 |

Equations solver categories